The Risk Assessment of Dam Construction Projects Using Fuzzy TOPSIS (Case Study: Alavian Earth Dam) - Sina Shaffiee Haghshenas; Mir Ahmad Lashteh Neshaei; Pouyan Pourkazem; Sami Shaffiee Haghshenas (Salehan Institute of Higher Education, 2016)
One of the appropriate tools for conducting a successful project is the risk management during the implementation of the project. Dam construction projects are complex projects with high impact factors such as variable and uncertain conditions. To identify the risks of project, experts' experiences and comments including mind storm and consultation sessions were used. Risk analysis is a complex issue. Therefore, in this paper, the fuzzy multiple criteria decision making (FMCDM) technique was used to rank the risk which is a powerful and effective tool in solving complex problems under uncertain and implicit conditions. Due to the uncertainty in the language, fuzzy data were used for the quantitative analysis of the probability and severity of effects and the repetition of risks taken into account. The present research was conducted on Alavian dam in the northeast of Iran. Due to the result of the study, design mistakes' risk (R4) has the highest level of risk and earthquake, etc. has the lowest level of risk in Alavian dam project.